2014
DOI: 10.1136/vr.102205
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium felis in faeces from cats in the UK

Abstract: Cryptosporidium spp. are protozoan parasites that can cause significant gastrointestinal disease in humans and animals. Cryptosporidium spp. are usually host-specific; cats are commonly infected with Cryptosporidium felis, but Cryptosporidium parvum and Cryptosporidium muris have also been reported (Scorza and Tangtrongsup 2010). The majority of the Cryptosporidium DNA amplified from 14,469 human faecal samples in the UK was Cryptosporidium hominis (51.4 per cent) or C parvum (44.0 per cent) (Elwin and others … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…In Sweden, the prevalence of Cryptosporidium infection in cats is not known, but the present observation that 18.5% (5/27) of fecal specimens from diarrheic cats with giardiasis were positive for C. felis suggests that occurrence of feline cryptosporidiosis is underestimated in this country. However, inasmuch as Cryptosporidium – Giardia co-infection seems to be rather common in cats, the observed rates must be interpreted with caution ( 22 , 26 , 27 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In Sweden, the prevalence of Cryptosporidium infection in cats is not known, but the present observation that 18.5% (5/27) of fecal specimens from diarrheic cats with giardiasis were positive for C. felis suggests that occurrence of feline cryptosporidiosis is underestimated in this country. However, inasmuch as Cryptosporidium – Giardia co-infection seems to be rather common in cats, the observed rates must be interpreted with caution ( 22 , 26 , 27 ).…”
Section: Discussionmentioning
confidence: 95%
“…Prevalence of Cryptosporidium in cats varies considerably, ranging from 0 to 29.4% depending on the population investigated and the evaluation methods used ( 21 , 22 ). In studies employing species identification, most cases of feline cryptosporidiosis have been attributed to C. felis , and detection of C. parvum or C. muris has only occasionally been reported ( 23 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Some enteric agents of cats that are infectious immediately in feces, like Giardia species or Cryptosporidium felis , are not considered significant zoonotic agents; when these infections occur, the strains are generally cat-specific. 1518…”
Section: Enteric Zoonosesmentioning
confidence: 99%
“…13,14 Some enteric agents of cats that are infectious immediately in feces, like Giardia species or Cryptosporidium felis, are not considered significant zoonotic agents; when these infections occur, the strains are generally cat-specific. [15][16][17][18] Other infectious agents, such as Ancylostoma species, Toxocara cati and Toxoplasma gondii, require a period of time out of the host prior to becoming infectious. Thus, many enteric zoonoses result from ingestion of the infectious agent in contaminated food, water or other environmental sources.…”
Section: Enteric Zoonosesmentioning
confidence: 99%
“…C. canis and its subgenotypes have been reported worldwide in dogs, foxes, coyotes, and humans (Fayer et al, 2001;Lucio-Forster et al, 2010;Elwin et al, 2012). It is generally species-specific, dogs are commonly infected with C. canis, and it has also been reported that they are infected with C. parvum (Scorza and Tangtrongsup, 2010;FitzGerald et al, 2011;Scorza et al, 2014). C. canis is often subclinical in dogs, and these dogs excrete oocysts without showing any clinical findings (Lindsay and Zajac, 2004;Scorza and Tangtrongsup, 2010;).…”
Section: Introductionmentioning
confidence: 99%